Peran Kolaboratif Guru dan Orang Tua dalam Mengembangkan Kemampuan Kognitif Anak Usia Dini - Maulina, Iin; Andriani, Feby; Dona, Dona (Innovative: Journal Of Social Science Research, 2025)
Collaboration between teachers and parents plays an important role in supporting the cognitive development of early childhood in kindergarten (TK). This study aims to explore the effectiveness of this collaboration through a literature study method. Data were collected from various academic sources to analyze the impact of collaboration on children's cognitive abilities, strategies applied, and challenges faced. The results of the study indicate that synergistic support between teachers and parents improves children's logical, critical, and creative thinking skills, through project-based learning activities, exploration, and consistent interactions between the school and home environments. Collaborative strategies such as intensifying communication, involving parents in learning activities, and strengthening learning at home have proven effective in creating a meaningful learning environment for children. However, challenges such as time constraints, differences in understanding, and access to technology are obstacles that need to be overcome. This study recommends the development of training programs for teachers and parents, as well as providing a digital platform to strengthen collaboration. With an integrated approach, collaboration between teachers and parents can optimize the cognitive development of early childhood, providing a strong foundation for Education.